Pengaruh Pendekatan Realistic Mathematics Education pada Pembelajaran Matematika Terhadap Literasi Matematika Siswa Kelas I di SDN Jember Kidul 04 Kabupaten Jember - Amelia Syarifa Sefina (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research aims to determine whether or not there is an influence of the realistic mathematics education approach in mathematics learning on the mathematical literacy of class I students at SDN Jember Kidul 04, Jember Regency. The type of research used was quasi experimental with a pretest-posttest control group design pattern. The data collection techniques used are documentation and tests. The data analysis techniques used are normality test, t-test, and relative effectiveness. Based on t-test calculations, the results showed that there was an influence of the realistic mathematical education approach in mathematics learning on the mathematical literacy of class I students at SDN Jember Kidul 04, Jember Regency. This is proven by the ER calculation results, namely 41.84% which is included in the medium category.
Entry oleh Arif 2026 Januari 29
Keywords: mathematics learning; realistic mathematics education; mathematical literacy